KETERAMPILAN GURU SOSIOLOGI DALAM MEMBUKA DAN MENUTUP PELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Siti Nurhalimah; Izhar Salim; Imran Imran (Universitas Tanjungpura, 2018)
AbstractThe title of this thesis is Sociology Teacher Skills in Opening and Closing Lessons to Improve Student Motivation in Class XI IPS SMAN 1 Sanggau District Hall. The general problem of this research is how sociology teacher skill in opening and closing lessons to improve student's learning motivation in class XI IPS SMA Negeri 1 Balai. The form of research used in this study is qualitative research with descriptive research method. Data collection techniques used were observation techniques, interviews and documentation studies, while data collection tools were observation guides, interview guides, and documentation studies. The results of the research (1) The sociology teacher's skill in opening lessons with the components include: attracting students' attention, generating motivation, giving reference, and making the relation / material relationship with good criteria. (2) The sociology teacher's skill in closing the lesson with the components of making conclusions, evaluating, and providing homework with good criteria. (3) Student learning motivation has increased with indicators that are diligently facing the task, tenacious face difficulties and prefer to work independently with good criteria.Keywords: Skills, Opening and Closing Lessons, Learning Motivation